Seeds for Needs - East Africa: Helping farming communities cope with the effects of climate change by providing access to locally adapted seeds - Gevel, Jeske M.J, van de; Fadda, Carlo; Bioversity International (2014)
The Seeds for Needs initiative works with farmers to research how agricultural biodiversity can help minimize the risks associated with climate change. At the same time Seeds for Needs is helping farming communities cope with the effects of climate change by providing access to locally adapted seeds. This poster gives an overview of the projects in East Africa. Activities are ongoing in Ethiopia, Tanzania, Kenya, Uganda and Rwanda.